Prenatal valproate in rodents as a tool to understand the neural underpinnings of social dysfunctions in autism spectrum disorder. (15th November 2019) - Tartaglione, Anna Maria; Schiavi, Sara; Calamandrei, Gemma; Trezza, Viviana
Abstract: Impairments in social interaction and verbal and non verbal communication are among the main features of Autism Spectrum Disorder (ASD). The causes of ASD are still unknown but the research efforts of the last decade have identified a number of factors (rare gene mutations, gene variations and adverse environmental events) that, interacting in complex ways, affect early brain development. The clinical evidence that prenatal exposure to the antiepileptic drug valproate (VPA) is associated with increased risk of neurodevelopmental delay, cognitive deficits and autism in children, has drawn the attention of scientists on VPA as a tool to unravel the environment contribution to ASD risk in children. In agreement with the clinical evidence, rodents prenatally exposed to VPA display behavioral anomalies resembling ASD symptoms. The mechanisms by which administration of VPA in pregnancy increases the risk of autism are still far to be clear as are still undetermined the specific targets of VPA in the developing brain both in humans and rodents. However, the robustness of the behavioral alterations, mainly in the social domain, and the neural/molecular changes revealed so far support the VPA model as a reliable instrument to investigate the neural underpinnings of social impairment. Here we provide an update of preclinical studies on prenatal exposure to VPA in rodents with a focus on the social and communication deficits induced by VPA, discussing potential pitfalls and future directions in this research field and corroborating the potential of the VPA model to identify new pharmacological targets for ASD. This article is part of the Special Issue entitled 'The neuropharmacology of social behavior: from bench to bedside'. Highlights: Prenatal VPA exposure is a risk factor for autism spectrum disorder (ASD). Prenatal VPA exposure is a preclinical model of ASD. VPA-exposed rodents show ASD-like social and communication deficits. The VPA model is a valuable tool to identify new pharmacological targets for ASD.